2017
DOI: 10.4314/sokjvs.v15i4.8
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of mycotoxigenic fungi in poultry feeds at live-bird markets, Zaria, Nigeria

Abstract: Contamination of poultry feeds with mycotoxin-producing fungi such as Aspergillus spp is a major threat to animal and human food. This study was conducted to determine the occurrence of aflatoxigenic strain of fungi in feeds, fed to birds in live-bird markets. Feed samples were collected from feeding troughs and feeder in cages of birds and were inoculated on Sabouraud dextrose agar and Czypeck dox agar. Of 300 feed samples, 283 yielded various fungal growth belonging to seven genera, four of them known to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
3
5
0
Order By: Relevance
“…From the above genera, the most prevalent species were A. flavus , A. niger , Aspergillus tamarii , Aspergillus terreus , Aspergillus versicolor , Emericella nidulans , Fusarium oxysporum , Mucor racemosus , Neurospora crassa , Paecilomyces variotii , Penicillium chrysogenum , and Rhizopus stolonifer (Table ). These results are in partial or complete agreement with those reported by several researchers in different places of the world (Azizi, Shateri, & Mousavizadeh, ; Figueroa, Conteno, Calvo, Rengel, & Adelantado, ; Ibrahim, Kabir, Kwanashie, Salawudeen, & Joshua, ; Krnjaja, Stojanovic, Cmiljanic, Trenkovski, & Tomasevic, ; Zohri, Saber, Youssef, & Abdel‐Kereem, ). Okoli et al () studied and identified the common molds growing in commercial poultry feed sold in Owerri, Nigeria.…”
Section: Resultssupporting
confidence: 91%
“…From the above genera, the most prevalent species were A. flavus , A. niger , Aspergillus tamarii , Aspergillus terreus , Aspergillus versicolor , Emericella nidulans , Fusarium oxysporum , Mucor racemosus , Neurospora crassa , Paecilomyces variotii , Penicillium chrysogenum , and Rhizopus stolonifer (Table ). These results are in partial or complete agreement with those reported by several researchers in different places of the world (Azizi, Shateri, & Mousavizadeh, ; Figueroa, Conteno, Calvo, Rengel, & Adelantado, ; Ibrahim, Kabir, Kwanashie, Salawudeen, & Joshua, ; Krnjaja, Stojanovic, Cmiljanic, Trenkovski, & Tomasevic, ; Zohri, Saber, Youssef, & Abdel‐Kereem, ). Okoli et al () studied and identified the common molds growing in commercial poultry feed sold in Owerri, Nigeria.…”
Section: Resultssupporting
confidence: 91%
“…But all studies strengthen the presence of opportunistic fungal species in poultry feed. A. flavus is common agricultural contaminants reported by Ismaiel and Papenbrock (2015) and Ibrahim et al (2017) in accord to present study findings. Above mentioned and current data of poultry feed reveals A. flavus a frequent contaminant of poultry feed.…”
Section: Discussionsupporting
confidence: 90%
“…Pre-enriched samples were subcultured on blood agar (Oxoid, UK) and Sabouraud dextrose agar (SDA) (Oxoid, UK) and incubated at 37°C and 25°C for 24 h and 3-4 days, respectively, for bacterial and fungal isolation. Bacterial growth on blood agar was subjected to biochemical reactions which include Gram staining, catalase, oxidase, Triple sugar iron, citrate utilization, and urease [ 11 ] while the fungal growth on SDA was identified using lactophenol cotton blue staining procedure [ 12 ]. Total bacterial count for the feed (1%) was carried out using the surface plating method.…”
Section: Methodsmentioning
confidence: 99%